Evaluation of Switch‐to‐Brand Rates as a Potential Signal for Therapeutic Equivalency of Generic Antidepressants: A Real‐World Retrospective Cohort Study. Issue 2 (27th April 2021) - Kalaria, Shamir; Spence, O'Mareen; Hong, Kyungwan; dosReis, Susan; Gopalakrishnan, Mathangi
Abstract : Negative clinical outcomes after switching from brand to generic antidepressants have raised concerns regarding therapeutic equivalency. This research aims to estimate the prevalence of switching and to identify predictors for generic to brand switching for various antidepressants. This retrospective cohort study utilized data from a 10% random sample of enrollees in the IQVIA PharMetrics Plus claims database from 2007–2015. The base cohort consisted of commercially insured patients who were prescribed escitalopram, duloxetine, or venlafaxine extended release (ER) anytime from the year prior to the generic launch through December 2014. The primary outcome was defined as a switch from generic to a brand within 14 days of sustained generic use in a 1‐year follow‐up period. Adjusted logistic regression and generalized estimating equations for repeated measures estimated the drug specific and overall odds of switch‐to‐brand among brand initiators relative to generic initiators, respectively. A total of 102, 831 unique patients across 3 drug products contributed to the final analytic sample. The overall prevalence of switch from generic to brand was 0.74%. Across all three antidepressants, brands initiators were more likely to experience a switch‐to‐brand: escitalopram (odds ratio (OR): 14.41, 95% confidence interval (CI): 11.14–18.64), duloxetine (OR: 8.08, 95% CI: 4.85–13.41) and venlafaxine ER (OR: 16.46, 95% CI: 11.56–23.46). The pooled odds of a switch‐to‐brand in brand vs. generic initiators was 13.77 (95% CI: 11.35–16.71). This study suggests a low overall switch‐to‐brand prevalence and may support therapeutic equivalence between brand and generic antidepressants. Initiating with a brand product was the strongest predictor for switching back to brand and suggests that patient experience may play a role in drug utilization.